Inovasi Pemanfaatan Serat Polypropylene dan Limbah Abu Cangkang Sawit sebagai Bahan Subtitusi Beton - Rizal Andika Saputra; Luthfi Helmi Pratama; Puji Widodo; Riza Susanti (Jurnal Sipil dan Arsitektur, 2023)
The existence of infrastructure development has increased rapidly in encouraging global competitiveness, including infrastructure development in Indonesia. In infrastructure development, there are many aspects that must be considered. The planning stage is the most important stage in infrastructure development, because it will determine the quality of the building to be produced. Therefore, infrastructure development in Indonesia must use good construction material design to improve the quality of buildings and minimize the impact of damage to buildings. One of the alternative efforts made is to improve the quality of building quality by utilizing materials that can reduce expensive development costs and are more environmentally friendly. The use of palm kernel shell ash and polypropylene fiber  waste can be an alternative solution to this problem.  The research method carried out is quantitative experimental conducted in the laboratory with variations in test objects in the form of (0% ACS; 0% PP); (6 % ACS;0% PP); (0 % ACS;6% PP); (3% ACS;3% PP) tested for compressive strength and flexural strength at 28 days concrete life. Palm kernel shell ash waste was chosen as an added material for concrete mixture because it has the same properties as cement, namely silica (SiO4), while polypropylene fiber  was chosen because it can function as  a filler that binds hollow concrete. From the research that has been done, several variations of test objects that have been made have been made then have gone through a testing process and compared to normal concrete K-300, modified  concrete (3% ACS; 3% PP) is concrete with optimum variations that are more efficient and have high quality in compressive and flexural strength test results, which are 31,174  MPa and 30 MPa from normal concrete quality results.